Reduction of the Number of Major Representative Allergens: From Clinical Testing to 3-Dimensional Structures - Ying He; Xueting Liu; Yuyi Huang; Zehong Zou; Huifang Chen; He Lai; Lida Zhang; Qiurong Wu; Junyan Zhang; Shan Wang; Jianguo Zhang; Ailin Tao; et al. (Mediators of Inflammation)
Vast amounts of allergen sequence data have been accumulated, thus complicating the identification of specific allergenic proteins when performing diagnostic allergy tests and immunotherapy. This study aims to rank the importance/potency of the allergens so as to logically reduce the number of allergens and/or allergenic sources. Meta-analysis of 62 allergenic sources used for intradermal testing on 3,335 allergic patients demonstrated that in southern China, mite, sesame, spiny amaranth, Pseudomonas aeruginosa, and house dust account for 88.0% to 100% of the observed positive reactions to the 62 types of allergenic sources tested. The Kolmogorov-Smironov Test results of the website-obtained allergen data and allergen family featured peptides suggested that allergen research in laboratories worldwide has been conducted in parallel on many of the same species. The major allergens were reduced to 21 representative allergens, which were further divided into seven structural classes, each of which contains similar structural components. This study therefore has condensed numerous allergenic sources and major allergens into fewer major representative ones, thus allowing for the use of a smaller number of allergens when conducting comprehensive allergen testing and immunotherapy treatments.